The iron wall : Israel and the Arab world - Shlaim, Avi (London, Allen Lane, 2000)
When Zionist leaders formulated the "Iron Wall" strategy in the 1920s they hoped that Israel would be able to make peace with its Arab neighbours. This has been an elusive hope. In this text, Shlaim explores the reason for Israel's long reliance on military power in the absence of a settlement.
Keywords: Israel; Arab-Israeli conflict; International relations; Diplomatic relations; Military policy -- Arab countries; Jewish-Arab relations